Morphological and Molecular Characterization of Eggs and Paralarvae of Green Octopus, Octopus hubbsorum Berry 1953, from the Gulf of California - Maritza García-Flores; Rosa María Morelos-Castro; Marcial Arellano-Martínez (Diversity, 2025)
The green octopus, Octopus hubbsorum, is a merobenthic species that inhabits warm-temperate waters in the eastern Pacific. However, its similarity to some morphological characteristics of and its slight genetic divergence from Octopus mimus has led to the proposal that both species are conspecific. The objective of this study was the morphological and molecular identification of eggs and paralarvae of the green octopus, O. hubbsorum, to provide information contributing to clarifying its taxonomy and relationship with O. mimus. The results obtained show that although O. hubbsorum has similarities with O. mimus in terms of egg size, chromatophore pattern, number of suckers, and presence of Kölliker’s organs, the O. hubbsorum paralarvae observed in this study are smaller (1.6 mm) and have a thin layer of loose skin, not described for O. mimus. Likewise, the morphology of the beak, radula, and suckers of O. hubbsorum is described for the first time and there are no studies of these structures for O. mimus. The phylogenetic analysis (mitochondrial cytochrome C oxidase subunit I and III genes) showed that both species form a monophyletic clade but belong to separate subclades. In conclusion, although the slight genetic divergence between these two species suggests conspecificity, their disjoint geographic distribution (O. hubbsorum is found in warm-temperate waters and O. mimus in cold-temperate waters) suggests the hypothesis of being two separate species with a close phylogenetic relationship. However, further research (morphological and population analyses) is required to solve taxonomic uncertainty.